Answer: 4x-12x
Step-by-step explanation:
Distributive preoperty so -6*-2/3=4 and -6*2x= -12x together 4x-12x equals option c
Answer:
A)

Step-by-step explanation:
Answer:
0
Step-by-step explanation:
f(0) = -2(0)²
= -2(0)
= 0
Answer:
6
Step-by-step explanation:
75−3.5y−4y=4y+6
Step 1: Simplify both sides of the equation.
75−3.5y−4y=4y+6
75+−3.5y+−4y=4y+6
(−3.5y+−4y)+(75)=4y+6(Combine Like Terms)
−7.5y+75=4y+6
−7.5y+75=4y+6
Step 2: Subtract 4y from both sides.
−7.5y+75−4y=4y+6−4y
−11.5y+75=6
Step 3: Subtract 75 from both sides.
−11.5y+75−75=6−75
−11.5y=−69
Step 4: Divide both sides by -11.5.
−11.5y
−11.5
=
−69
−11.5
y=6
Hope this helps!